Β3 Integrin Promotes Long-Lasting Activation and Polarization of Vascular Endothelial Growth Factor Receptor 2 by Immobilized Ligand. Issue 10 (October 2015) - Ravelli, Cosetta; Grillo, Elisabetta; Corsini, Michela; Coltrini, Daniela; Presta, Marco; Mitola, Stefania
Abstract : Objective—: During neovessel formation, angiogenic growth factors associate with the extracellular matrix. These immobilized factors represent a persistent stimulus for the otherwise quiescent endothelial cells (ECs), driving directional EC migration and proliferation and leading to new blood vessel growth. Vascular endothelial growth factor receptor 2 (VEGFR2) is the main mediator of angiogenesis. Although VEGFR2 signaling has been deeply characterized, little is known about its subcellular localization during neovessel formation. Aim of this study was the characterization and molecular determinants of activated VEGFR2 localization in ECs during neovessel formation in response to matrix-immobilized ligand. Approach and Results—: Here we demonstrate that ECs stimulated by extracellular matrix–associated gremlin, a noncanonical VEGFR2 ligand, are polarized and relocate the receptor in close contact with the angiogenic factor–enriched matrix both in vitro and in vivo. GM1 (monosialotetrahexosylganglioside)-positive planar lipid rafts, β3 integrin receptors, and the intracellular signaling transducers focal adhesion kinase and RhoA (Ras homolog gene family, member A) cooperate to promote VEGFR2 long-term polarization and activation. Conclusions—: A ligand anchored to the extracellular matrix induces VEGFR2 polarization in ECs. Long-lasting VEGFR2 relocation is closely dependent on lipid raft integrity and activation of β3 integrin pathway. The study of the endothelial responses to immobilized growth factors may offer insights into the angiogenic process in physiological and pathological conditions, including cancer, and for a better engineering of synthetic tissue scaffolds to blend with the host vasculature. Abstract : Supplemental Digital Content is available in the text.